Correlation between Voronoi volumes in disc packings - Schröter, Matthias; Zhao, Song-Chuan; Sidle, Stacy; Swinney, Harry L. (EPL - Europhysics Letters, 2012)
We measure the two-point correlation of free Voronoi volumes in binary disc packings, where the packing fraction phi(avg) ranges from 0.8175 to 0.8380. We observe short-ranged correlations over the whole range of phi(avg) and anticorrelations for phi(avg) > 0.8277. The spatial extent of the anticorrelation increases with phi(avg) while the position of the maximum of the anticorrelation and the extent of the positive correlation shrink with phi(avg). We conjecture that the onset of anticorrelation corresponds to dilatancy onset in this system. Copyright (C) EPLA, 2012